The Psychology Of Travel Behaviour In The Select Novels Of Emilybarr - Ms. R. Seemapriya; Dr. S. Sudha; Dr. R. Vithya Prabha (The Bioscan, 2025)
The psychology of travel behaviour is a complex field that examines the cognitive, emotional, and social factors influencing an individual’s travel decisions and activities. This area of study may seek to comprehend the reasons behind their travel choices, planning processes, the motivations driving their journeys, and the overall travel experience. The psychology of travel behaviour continues to evolve, as global mobility increases and societal values shift. “Traveling tends to magnify all human emotions.” asserts Peter Hoeg, a Danish writer, unveiling the individual’s genuine reactions, preferences, and abilities amid travelling.